A Comparative Study of Time-Frequency Representations for Bearing and Rotating Fault Diagnosis Using Vision Transformer - Orhan, Ahmet; Yordanov, Nikolay; Ertargin, Merve; Zhilevski, Marin; Mikhov, Mikho (Mdpi, 2025)
This paper presents a comparative analysis of bearing and rotating component fault classification based on different time-frequency representations using vision transformer (ViT). Four different time-frequency transformation techniques-short-time Fourier transform (STFT), continuous wavelet transform (CWT), Hilbert-Huang transform (HHT), and Wigner-Ville distribution (WVD)-were applied to convert the signals into 2D images. A pretrained ViT-Base architecture was fine-tuned on the resulting images for classification tasks. The model was evaluated on two separate scenarios: (i) eight-class rotating component fault classification and (ii) four-class bearing fault classification. Importantly, in each task, the samples were collected under varying conditions of the other component (i.e., different rotating conditions in bearing classification and vice versa). This design allowed for an independent assessment of the model's ability to generalize across fault domains. The experimental results demonstrate that the ViT-based approach achieves high classification performance across various time-frequency representations, highlighting its potential for mechanical fault diagnosis in rotating machinery. Notably, the model achieved higher accuracy in bearing fault classification compared to rotating component faults, suggesting higher sensitivity to bearing-related anomalies.
Keywords: bearing fault classification; rotating component fault classification; short-time Fourier transform; continuous wavelet transform; Hilbert-Huang transform; Wigner-Ville distribution; vision transformer